The Effect of Inflation, Exchange Rate, Implementation of Good Corporate Governance (GCG), and Financing to Deposit Ratio (FDR) on Sharia Commercial Bank Financing Risks in Indonesia 2019-2022 - Orsita Asmu Putri; Putri, Rizky Nur Ayuningtyas (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2023)
The large number of products offered by banks, especially financing,causes greater potential risks that will occur which can be influencedby various factors. Therefore, the aim of this research is to determinethe influence of Inflation, Exchange Rates, Implementation of GoodCorporate Governance (GCG), and Financing to Deposit Ratio (FDR) ininfluencing Financing Risk as proxied by Non-Performing Financing(NPF) in Commercial Banks Sharia in Indonesia 2019-2022. The dataused in the research is secondary data, namely annual financialreports and Good Corporate Governance (GCG) reports for 2019-2022. The population of this research is Islamic commercial banks inIndonesia with a sampling technique, namely purposive sampling. Theregression analysis method used is panel data using Eviews 10. Theresearch results show simultaneously that Inflation, Exchange Rates,Good Corporate Governance (GCG) have a significant effect on Non-Performing Financing (NPF). However, partially it shows that (1)Inflation, Exchange Rates, and Financing to Deposit Ratio (FDR) haveno effect on Non-Performing Financing (NPF), (2) Good CorporateGovernance (GCG) has a significant positive effect on Non-PerformingFinancing (NPF).